Analysis of enamel and material wear by digital microscope: an in-vitro study - Syed Rashid Habib; Abdul Sadekh Ansari; Mohammed Alqahtani; Ibrahim F Alshiddi; Abdulaziz S Alqahtani; Syed Hammad Hassan
Abstract: The objective of the study was to analyze the surface area (SA) of the wear caused by simulated chewing on human enamel and opposing restorative material, namely: composite resin (CR), porcelain fused to metal (PFM), lithium disilicate (LD), or monolithic zirconia (MZr). Forty-eight premolars were selected as enamel specimens and divided randomly into 4 groups (n = 48; n =12) used as antagonists in chewing simulation (250,000 loading cycles) against one of the four selected test materials. Enamel and material specimens were scanned and evaluated under digital microscope, and wear SA (mm2) were recorded. Descriptive statistics, paired t-test, one-way ANOVA, and post-hoc Tukey-HSD tests were used for statistics (p < 0.05). The smallest and largest SA were exhibited by enamel against LD (0.80 mm2) and PFM (1.74 mm2), respectively. PFM (3.48 mm2) showed the largest SA and CR (2.28 mm2) showed the smallest SA. Paired t-test for SA values showed significant difference (p < 0.05) in all wear comparisons between materials and enamel antagonists. The wear of materials were greater than that of their respective enamel antagonists (p < 0.05). One-way ANOVA of the logarithmic means of wear SA revealed significant differences (P<0.05). Post-hoc Tukey test revealed significance for PFM (p < 0.05) with other materials. Wear of all test materials was greater compared to the wear of enamel antagonists. PFM and LD caused the largest and the smallest enamel wear, respectively. CR, LD, and MZr are more resistant than PFM to wear after simulated chewing against enamel.